A Minimalist Account of Structural Case Assignment in Pashto Unergative Constructions - Masood, Talat; Rahman, Mujib (Journal of humanities and social sciences (Peshawar, Pakistan), 2013)
Pashto unergatives, like other Pashto constructions, are characterized by splitergativity with reference to tense; thus the subject nominal shows the nominative Case in the present and the future tenses, and the accusative Case in the past tense which requires the assignment of the two Cases by two different functional heads. Following the minimalist idea of agreement, we propose, for Pashto unergative constructions, that nominative Case to subject nominals is assigned as a result of co-features agreement between the functional head T and the subject nominals, while accusative Case is assigned as a result of [straight phi]-features agreement with the functional head Voice; as υ in the past tense Pashto constructions is defective in the Chomskian (2001) sense. The overall conclusion for Case assignment in Pashto unergative constructions is that the minimalist idea of agreement between a nominal and a functional head as responsible for structural Case assignment is equally applicable to Pashto unergative Constructions.